Pengaruh Bonus Plan, Net Profit Margin, Cash Holding, Nilai Perusahaan, Dan Institutional Ownership Terhadap Perataan Laba (Income Smoothing) - Elvina Resti Fauziyah; Fatchan Achyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Income Smoothing is an accounting strategy used by company management to reduce profit fluctuations from one period to another. The objective of this practice is to create the impression that the company has stable and predictable performance, thereby enhancing the confidence of investors, creditors, and other stakeholders. This study aims to analyze the effect of bonus plans, net profit margin (NPM), cash holding, firm value, and institutional ownership on income smoothing in infrastructure companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. This research employs a quantitative method with a purposive sampling approach in sample selection. Data is obtained through documentation methods from the official IDX website and relevant company websites. The data analysis techniques used include descriptive analysis and logistic regression analysis with the assistance of SPSS software. The results indicate that cash holding and institutional ownership have a significant effect on income smoothing, while bonus plans, net profit margin, and firm value do not influence income smoothing.